Two scene navigation systems dissociated by deliberate versus automatic processing. (July 2021) - Suzuki, Shosuke; Kamps, Frederik S.; Dilks, Daniel D.; Treadway, Michael T.
Abstract: Successfully navigating the world requires avoiding boundaries and obstacles in one's immediately-visible environment, as well as finding one's way to distant places in the broader environment. Recent neuroimaging studies suggest that these two navigational processes involve distinct cortical scene processing systems, with the occipital place area (OPA) supporting navigation through the local visual environment, and the retrosplenial complex (RSC) supporting navigation through the broader spatial environment. Here we hypothesized that these systems are distinguished not only by the scene information they represent (i.e., the local visual versus broader spatial environment), but also based on the automaticity of the process they involve, with navigation through the broader environment (including RSC) operating deliberately, and navigation through the local visual environment (including OPA) operating automatically . We tested this hypothesis using fMRI and a maze-navigation paradigm, where participants navigated two maze structures ( complex or simple, testing representation of the broader spatial environment) under two conditions ( active or passive, testing deliberate versus automatic processing). Consistent with the hypothesis that RSC supports deliberate navigation through the broader environment, RSC responded significantly more to complex than simple mazes during active, but not passive navigation. By contrast, consistent with the hypothesis that OPA supports automatic navigation through the local visual environment, OPA responded strongly even during passive navigation, and did not differentiate between active versus passive conditions. Taken together, these findings suggest the novel hypothesis that navigation through the broader spatial environment is deliberate, whereas navigation through the local visual environment is automatic, shedding new light on the dissociable functions of these systems.